Pengaruh Technical Quality dan Functional Quality Terhadap Kepuasan Pengunjung Situs Yahoo! - Sadana Devica (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2014)
The purpose of this study is to investigate and analyze the effect of the variable quality of service to the satisfaction of both the Yahoo! site visitors simultaneously or partially, and to investigate the variable quality of service that the dominant influence on the Yahoo! site visitor satisfaction. This type of research is the explanatory research with a survey method. The independent variables consists of technical quality and functional quality, as well as the dependent variable is the Yahoo! site visitor satisfaction. The samples studied were students totaling 100 respondents. The results of multiple regression analysis showed that the quality of service significantly influence the Yahoo! site visitor satisfaction either simultaneously or partially. Technical quality and functional quality variables have a positive relationship or the direction of the Yahoo! site visitor satisfaction. From the analysis it can be seen that the technical quality of the dominant influence on the Yahoo! site visitor satisfaction.